Economic Value Added and External Financing Needs on Firm Value with Good Corporate Governance in Technology Sector Companies - Putu Wahyu Permana Arta; I Made Pradana Adiputra; Ni Kadek Sinarwati (Economic and Business Horizon, 2026)
Firm value in Indonesia’s technology sector remains fluctuating and unstable despite the sector’s high growth potential. This condition raises questions regarding the role of economic value added, external financing needs, and good corporate governance in influencing firm value. The purpose of this study is to analyze the effect of economic value added and external financing needs on firm value and to examine the moderating role of good corporate governance in technology sector companies listed on the Indonesia Stock Exchange. This research employs a quantitative approach using panel data from 24 companies over the 2021–2024 period. Data analysis is conducted using a random effect model regression with classical assumption tests and moderated regression analysis. The results show that economic value added has a negative and significant effect on firm value, while external financing needs have no significant effect. In addition, good corporate governance does not strengthen the relationship between external financing needs and firm value but weakens the relationship between economic value added and firm value. The conclusion indicates that firm value in the technology sector is more strongly driven by growth expectations and market dynamics rather than traditional financial indicators and corporate governance mechanisms.